Emerging Perspectives in Cropping System–based Nutrient Management: A Scientometric Analysis: A scientometric analysis of cropping system-based nutrient management - Chaudhary, Amresh; Rai, Arvind Kumar; Yadav, Gajender; Kumar, Manish; Kumar, Jitendra; Chandra, Priyanka; Sundha, Parul (Journal of Soil Salinity and Water Quality, 2025)
In a world grappling with the dual challenge of feeding a burgeoning global population and safeguarding the environment, nutrient management in agricultural systems has emerged as a critical area of research and innovation. Cropping system-based nutrient management plays a crucial role in sustainable agriculture by optimizing nutrient utilization, enhancing crop productivity, and minimizing environmental impacts. In this context, this study aims to provide a comprehensive overview of recent advances in cropping system-based nutrient management strategies. It highlights the integration of various techniques, including precision agriculture, cover cropping, crop rotation, site-specific nutrient management and digital technologies, to improve nutrient use efficiency and mitigate nutrient-related challenges. Through an in-depth analysis of current research, this study emphasizes the importance of tailored nutrient management approaches that consider soil conditions, crop requirements, and environmental sustainability. It also emphasizes the urgent need for further research and widespread adoption of these strategies to ensure food security and environmental preservation. This paper presents a meticulous scientometric analysis spanning the past two decades (2003-2023) to comprehensively examine recent advances in cropping systems-based nutrient management. Drawing upon an extensive body of scientific literature, our analysis unveils key trends, influential research, and emerging areas of interest within this field. We identified a paradigm shift towards precision agriculture, integrated nutrient management, and sustainable farming practices as dominant themes. We found that Indian scientists from IARI are publishing many research papers on the given topic. The Indian Journal of Agronomy and Indian Journal of Agricultural Sciences are leading publishers for articles on nutrient management and cropping systems. Long-term carbon sequestration, organic manure and nutrient use efficiency are trending topics of research, while soil carbon sequestration and analysis of soil carbon pools under different cropping systems are emerging topics of research. By synthesizing the collective wisdom of the past two decades, the current study informs the strategic allocation of resources and the formulation of research priorities, thereby catalysing innovative solutions to the complex challenges at the intersection of food security and environmental sustainability.